Toastmaster's treasure chest - Prochnow, Herbert V.; Prochnow, Herbert V. Jr. (New York Harper & Row, Publishers, 1979)
Provides a wealth of material for use before audiences of many kinds, including humorous stories, contemporary quotations, epigrams, witticisms, proverbs, great thoughts of famous Americans, amusing definitions, and more.
Humorous stories, Anecdotes, and Verse - Interesting and useful quotations - The wit and wisdom of famous persons - Unusual facts, stories, and quotations from biography - Inspirational quotations and illustrations - Epigrams and witticisms on many subjects - Helpful verses - Great thoughts of distinguished Americans - Humorous and unusual definitions - toasts and quotations for special occasions - The proverbs of many nations
Includes index
49895
Keywords: Public speaking -- Handbooks, manuals, etc; Wit and humor; Quotations, English